Integrated phenotypic screening and chemical proteomics identifies ETF1 ligands that modulate viral translation and replication - Arthur S. Kim; Kevin Ma; Christopher J. Reinhardt; Daniel C. Lazar; Daisuke Ogasawara; Teressa M. Shaw; Juan Carlos de la Torre; Adam L. Bailey; Bruno Melillo; John R. Teijaro; Benjamin F. Cravatt (Proceedings of the National Academy of Sciences, 2026)
Emerging and reemerging viruses pose a significant threat to global health. Although direct-acting antivirals have shown success, their efficacy is limited by the rapid emergence of drug-resistant viral variants. Hence, there is an urgent need for additional broad spectrum antiviral therapeutic strategies. Here, we identify by phenotypic screening a set of stereochemically defined photoreactive small molecules (photo-stereoprobes) that stereoselectively suppress SARS-CoV-2 replication in human lung epithelial cells. Structure–activity relationship–guided chemical proteomics identified the eukaryotic translation termination factor 1 (ETF1) as a target of the photo-stereoprobes, and this interaction was recapitulated with recombinant purified ETF1. We found that the photo-stereoprobes modulate programmed ribosomal frameshifting mechanisms essential for SARS-CoV-2 infection without causing ETF1 degradation, thus distinguishing the photo-stereoprobes from other known ETF1-directed small molecules. We finally show that the photo-stereoprobes also inhibit the replication of additional viruses with noncanonical ribosomal frameshifting mechanisms. Our findings identify a mechanistically distinct class of ETF1 ligands that implicate host translation termination processes as a potential drug target for antiviral development.